Teucrium × gutierrezii a new hybrid from Southeast Iberian Peninsula, a hotspots of natural hybridization of subfamily Ajugoideae (Lamiaceae) - Ruiz, Carlos Rubí; Navarro, Teresa (Phytotaxa, 2023)
A new nothospecies, Teucrium × gutierrezii, is described as result of the natural hybridization processes between two species of T. sect. Polium: T. eriocephalum subsp. almeriense (subsect. Simplicipilosa) and Teucrium lusitanicum subsp. lusitancum (subsect. Polium) both endemic from Iberian Peninsula. A morphological description with the diagnostic taxonomic differences between the new hybrid and the parental is provided as well as information about distribution, ecology and phenology for the new hybrid. In this paper we highlight the importance of hybridization in Teucrium in the Southeast Iberian Peninsula as drivers of diversity for Ajugoideae in the temperate Mediterranean regions.